Incidence of Congenital Heart Disease among Hospital Live Birth in a Tertiary Hospital of Bangladesh (Cardiovascular Journal, 2011)
Background: Incidence of congenital heart disease is 8-10/1000 live birth which is established by many studies carried out in many centers worldwide. In Bangladesh no incidence study was carried out so far. Newborn children presenting with various forms of congenital heart disease is a common problem now a days. Neonatologists and paediatricians are now more conscious about early detection and treatment of newborn with congenital heart diseases. Diagnostic facilities are also available in many places. So an individual incidence record from an ideal center of our country is a demand of the time which led carrying out this study. Methods: This prospective study was carried out in Combined Military Hospital (CMH) Dhaka over a period of three years (2004 – 2006). All five thousand six hundred and sixty eight live births weighing more than 500 gm and more than 28 weeks gestational period were subjected to a thorough clinical examination within 72 hours of birth. Those suspected to have any form of congenital heart disease (CHD) were followed up every 4-6 wks for a period of 12 months. Echocardiography with color Doppler was performed in all these newborn including those who reported late but were delivered in obstetrics department of Combined Military Hospital Dhaka. Result: One hundred forty two babies out of 5668 live birth had CHD, ie, 25/1000 live births. Incidence of CHD was higher in pre terms as compared to full term live birth. Some of the patients (18.30%) has other associated somatic anomalies among which Down’s syndrome was commonest (9.15%). Most common congenital heart lesions were Atrial Septal Defect (ASD-26%), Ventricular Septal Defect (VSD-16.9%), Patent Ductus Arteriosus (PDA-18%), Tetralogy of Fallot (TOF-14%), Pulmonary Stenosis (PS-7.75%) etc. Those who were found to have congenital heart disease were managed accordingly. Some patients had spontaneous closure of defects in first year follow up period. Conclusion: The incidence of Congenital Heart Disease (CHD) depends upon various factors like nature of the samples (all live birth or all birth) or on the spot examination by a Paediatric cardiologist. A hospital which has Obstetric, Neonatal and Paediatric cardiology unit can carried out this kind of study successfully. In this study screening of asymptomatic high risk neonates also contributes in early detection of many trivial lesions. Severe lesions were also detected by the paediatric cardiologist who usually expire before being referred from other hospitals and before being diagnosis is established. So a higher incidence rate is recorded in this study. Key words: Congenital heart disease; Echocardiography DOI: http://dx.doi.org/10.3329/cardio.v1i1.8199 Cardiovasc. j. 2008; 1(1) : 14-20